Critical Review of Healthcare Policy Reforms and Their Impact on Health Outcomes across Socioeconomic Groups - Alqahtani, Safar Mohammed Mushabab; Alqahtani, Sultan Abdullah Hussain; Asiri, Fahad Yahya Mohammed; Asiri, Ali Abdullah Yahya; Asiri, Tariq Ahmed Hassan; Asiri, Mohammed Ali Mohammed; alqhtani, Mofareh Tourkey Mohammed; Al Mawtah, Mohammed Ibrahim Binali; Alzabadani, Mansour Ali Hamad; Balhareth, Ali Abdulkarim Ali (Journal of Ecohumanism, 2024)
Universal healthcare policy changes are vital in the fight against differentiated healthcare debts along the line of provision. Stakeholder activities seek to enhance reception, costs, and quality of treatment; nevertheless, effectiveness differs based on other factors, for example, execution modalities, funding, and targeted populace. It discusses and analyzes healthcare policy reforms across countries and compares the results of their impact on health status and the equity in utilization and benefits received by people of different socioeconomic statuses. It also looks at how the use of technology and public-private partnerships enhances equity in health care delivery.